2020
DOI: 10.1182/bloodadvances.2019000955
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-related cardiotoxicity in older patients with acute myeloid leukemia: a Young SIOG review paper

Abstract: The incidence of acute myeloid leukemia (AML) increases with age. Intensive induction chemotherapy containing cytarabine and an anthracycline has been part of the upfront and salvage treatment of AML for decades. Anthracyclines are associated with a significant risk of cardiotoxicity (especially anthracycline-related left ventricular dysfunction [ARLVD]). In the older adult population, the higher prevalence of cardiac comorbidities and risk factors may further increase the risk of ARLVD. In this article of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 138 publications
(146 reference statements)
1
19
0
1
Order By: Relevance
“…Interestingly, comparing acute leukemia (AL) patients with other cancer patients, it has been reported that AL is linked to myocardial dysfunction 115 . Moreover, the rate of AL patients who develop heart failure significantly increases upon chemotherapy 116 , 117 . Consequently, although leukemia patients do not commonly develop cachexia 118 , the associated cardiac dysfunction may result in an increased susceptibility of AL patients to the development of the wasting syndrome.…”
Section: Inter- and Intracellular Mediators Of Skeletal And Heart Musmentioning
confidence: 99%
“…Interestingly, comparing acute leukemia (AL) patients with other cancer patients, it has been reported that AL is linked to myocardial dysfunction 115 . Moreover, the rate of AL patients who develop heart failure significantly increases upon chemotherapy 116 , 117 . Consequently, although leukemia patients do not commonly develop cachexia 118 , the associated cardiac dysfunction may result in an increased susceptibility of AL patients to the development of the wasting syndrome.…”
Section: Inter- and Intracellular Mediators Of Skeletal And Heart Musmentioning
confidence: 99%
“…Die akute myeloische Leukämie (AML) ist insbesondere eine Erkrankung des älteren Patienten, daher sind kardiale Komorbiditäten häufig Therapie-limitierend oder erschwerend. Erschwerend scheint eine Anthrazyklin-induzierte Kardiomyopathie (AiK) bei dieser Entität häufiger zu sein [1]. Eine mögliche kausale Verbindung ist die klonale Hämatopoese von unbestimmtem Potential (CHIP), welche zur Entstehung von Leukämien [2, 3] als auch kardiovaskulären Ereignissen [4, 5] prädisponiert.…”
Section: Transfer In Die Praxis Von Dr Nina Rosa Neuendorff (Essen)unclassified
“…14 Comorbid conditions, such as cardiac diseases, arterial hypertension, diabetes, dyslipidemia, and renal failure, are also significant risk factors. 15,16 Patients treated with anthracyclines are five times more likely to have reduced left ventricular ejection fraction or develop HF compared with those treated with other non-anthracycline chemotherapy. 4 AIC can be acute or chronic, with acute cardiotoxicity occurring during the treatment or immediately afterward; this entails pericarditis-myocarditis and arrhythmias, which are both possibly reversible.…”
Section: Anthracyclines and Cardiotoxicitymentioning
confidence: 99%
“…Other factors, such as female sex, age above 60 years, pediatric population, and previous radiotherapy have also been associated with a higher risk of cardiotoxicity 14 . Comorbid conditions, such as cardiac diseases, arterial hypertension, diabetes, dyslipidemia, and renal failure, are also significant risk factors 15,16 …”
Section: Anthracyclines and Cardiotoxicitymentioning
confidence: 99%